2009
DOI: 10.1093/humrep/dep396
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intramural fibroids without uterine cavity involvement on the outcome of IVF treatment: a systematic review and meta-analysis

Abstract: The presence of non-cavity-distorting intramural fibroids is associated with adverse pregnancy outcomes in women undergoing IVF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
2
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(173 citation statements)
references
References 39 publications
3
156
2
12
Order By: Relevance
“…Subsequent to our meta-analysis, another meta-analysis [44] was performed, this time including the study by Bozdag et al [43••]. Findings were similar to those in our systematic review.…”
Section: The Datasupporting
confidence: 83%
“…Subsequent to our meta-analysis, another meta-analysis [44] was performed, this time including the study by Bozdag et al [43••]. Findings were similar to those in our systematic review.…”
Section: The Datasupporting
confidence: 83%
“…The frequency of T-carriers genotypes was found significantly higher among the women with PE than the control groups indicated that MTHFR C677T polymorphism would be expected to play a major role to bring about PE. Some studies reported significantly increased prevalence of MTHFR C677T among cases [22][23][24]49]. In contrast, other 1 9 9 7 J a p a n A s i a n Three meta-analysis summarizing studies on association between the MTHFR C677T polymorphism and the risk of PE until August 2012 have been performed [51][52][53], however, their meta-analysis did not perform analyses on association between the MTHFR A1298C and the risk of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggest there is doubtful evidence of performing myomectomy in asymptomatic patients. 19,20 It can be performed laparoscopically or hysteroscopically depending on the location of fibroid. Though uterine septum mostly associated with the recurrent abortion and not with infertility we report an incidence of 42 (12.61%) patients with infertility.…”
Section: Discussionmentioning
confidence: 99%